2015
DOI: 10.4236/jbm.2015.36007
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Blood Glucose Measurement Based on NIR Spectrums and Double ANN Analysis

Abstract: This paper presents a new noninvasive blood glucose monitoring method based on four near infrared spectrums and double artificial neural network analysis. We choose four near infrared wavelengths, 820 nm, 875 nm, 945 nm, 1050 nm, as transmission spectrums, and capture four fingers transmission PPG signals simultaneously. The wavelet transform algorithm is used to remove baseline drift, smooth signals and extract eight eigenvalues of each PPG signal. The eigenvalues are the input parameters of double artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Experiments showed that the RMSE of the prediction is between 0.97 and 6.69 mg/dL and the average of RMSE is 3.80 mg/dL. [ 24 ] Tamilselvi and Ramkumar in 2015 proposed a framework for noninvasive blood glucose measurement using NIR spectroscopy with 940-nm wavelength. At the start of experiment, the Global Positioning System module sends the user's position coordinates with the message to the physician.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiments showed that the RMSE of the prediction is between 0.97 and 6.69 mg/dL and the average of RMSE is 3.80 mg/dL. [ 24 ] Tamilselvi and Ramkumar in 2015 proposed a framework for noninvasive blood glucose measurement using NIR spectroscopy with 940-nm wavelength. At the start of experiment, the Global Positioning System module sends the user's position coordinates with the message to the physician.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the ineffectiveness of invasive techniques, non-invasive techniques for detecting blood sugar have emerged, this non-invasive technique is already quite widely used by implementing various types of calculation techniques. [2][3] [4] and the most widely used technique is linear regression techniques [5] [6]. Detection results produced through non-invasive devices do not have a high degree of accuracy and the level of error margins of noninvasive devices is still quite large.…”
Section: Introductionmentioning
confidence: 99%